Healthy eating index in a nationally representative sample of children and adolescents by socio-demographic characteristics: the Weight disorders survey of the CASPIAN-IV Study - Karimi, Golgis; Heidari-Beni, Motahar; Riahi, Roya; Qorbani, Mostafa; Kelishadi, Roya (The Turkish Journal of Pediatrics, 2020)
Background. To date, the diet quality of Iranian students in relation to socio-demographic characteristics was not studied. The present study aimed to explore the association between the healthy eating index and sociodemographic characteristics among a nationally representative sample of Iranian children and adolescents. Methods. This nationwide study was conducted in 5187 children and adolescents, aged 6-18 years. Data regarding socio-demographic variables, lifestyle factors, family and student dietary habits, and quality of life were gathered via validated questionnaires. The Alternate Healthy Eating Index-2010 (AHEI-2010) was used to calculate diet quality scores. Results. The odds of high diet quality was 24% lower in adolescents (13-18years) compared to children aged 6-12 years (OR 0.76, CI 0.64-0.89, p= 0.001). Students in families with moderate (OR 1.30, CI 1.13-1.49, p < 0.001) and high socioeconomic status (OR 1.36, CI 1.18-1.57, p < 0.001) were 30% and 36% more likely to have a higher diet quality score, respectively. Lower mean AHEI-2010 scores (CI) were found for low socio-economic status (46.18-47.10), adolescents 47.40 (46.94-47.82), boys 47.51 (47.14-47.88) and South-East area 47.19 (46.54-49.15) (p < 0.05) due to lower intake of fruits and vegetables and high intake of sodium and sugar-sweetened beverages. Conclusions. The overall diet quality of Iranian children and adolescents was low with disparities across sociodemographic variables notably age and familial socio-economic status.